PENGELOLAAN FASILITAS RUMAH MAKAN DI PANTAI TIRAM KABUPATEN PADANG PARIAMAN - Sari, Marnita; Yuliana, Yuliana; Pramudia, Heru (Journal of Home Economics and Tourism, 2017)
This study aims to describe the Management (planning, organizing, directing and supervision) Dining Facilities at Oyster Beach Padang Pariaman Regency which includes: dining and drinking facilities and supporting facilities. This research is a descriptive research with qualitative data. Technique of collecting data is done by using method of interview and observation. In this study using purposive sampling involving informants are: two managers and five employees of the restaurant. Data were analyzed through data reduction, data presentation and conclusion. The results of this study show that: 1) Each gazebo is occupied by a maximum of 8 people. 2) There is no plan to make air circulation and artificial lighting in the gazebo. 3) There is no plan to create menu list at restaurant. 4) The way managers organize restaurant facilities is by assigning workers to do work at the restaurant. 5) The way managers direct workers is by holding meetings on a regular basis by involving all workers and giving direction to workers in doing the work. 6) The way managers supervise workers is by supervising and monitoring workers directly in completing their work.Keywords: Management, Restaurant Facilities, Oyster Beach